A theoretical analysis of temperature rise of hydrogen in high-pressure storage cylinder during fast filling process. (December 2020) - LI, Ji-Qiang; Myoung, No-Seuk; Kwon, Jeong-Tae; Jang, Seon-Jun; Lee, Taeckhong; Lee, Yong-Hun
During the fast filing process, thermal stress is generated due to the increase in the pressure and temperature of hydrogen in the hydrogen storage tank. For its safety purpose, it is necessary to predict and control the temperature change in the tank. The aim of this study is quantitative analysis of the final temperature and the mass of the hydrogen in the tank through experimental and theoretical methods. In this paper; Theoretical model for adiabatic and non-adiabatic real filling processes of high pressure hydrogen cylinder has been proposed. The cycle of filling process from the initial vacuum state is called the "First cycle." After the first cycle is completed, there is a certain residual pressure in the tank. Then the second filling process called "Second cycle" begins. The final temperature in fast filling of hydrogen storage cylinders depends on targeted pressure, initial pressure and temperature, and mass filling rate. The final temperature of hydrogen in the tank was calculated from the real gas equation of state, mass and energy conservation equations. As a result of the analysis, based on the first cycle analysis of high pressure tank, the final temperatures were calculated to be 442.11 K for the adiabatic filling process, and 422.37 K for the non-adiabatic process. Based on the second cycle analysis of high pressure tank, the final temperature were obtained as 397.12 K and 380.8 K for the adiabatic and non-adiabatic processes, respectively. The temperatures calculated from the theoretical non-adiabatic condition were lower than those from the adiabatic condition by 5%. The results of this study can provide a reference basis in terms of how to control the temperature in the actual hydrogen storage tank during the fast filling process and how to improve safety.